2015
DOI: 10.1136/bmjquality.u205385.w4127
|View full text |Cite
|
Sign up to set email alerts
|

A simple prioritisation system to improve the electronic handover

Abstract: The General Medical Council (GMC) states, “A well managed, thorough and organized handover is crucial for ensuring the quality and safety for patient care,” and in their guidance on safe handover the British Medical Association (BMA) advised that “clinically unstable patients are known to the senior and covering clinicians; tasks should be prioritised; plans for further care are put in place; unstable patients are reviewed.”The orthopaedic department at King's College Hospital, a busy major trauma centre in Lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 4 publications
0
0
0
Order By: Relevance
“…This met minimum standards set by guidelines, and is an integral part of any handover. [3,7,8,12] There was always prioritisation of patients handed over, since the handover solely includes POC. Beyond this, there was no specific order to the patients discussed; however, unwell patients were sometimes further prioritised, to allow the Registrar to review them immediately after handover.…”
Section: Interpretation Within the Context Of The Wider Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…This met minimum standards set by guidelines, and is an integral part of any handover. [3,7,8,12] There was always prioritisation of patients handed over, since the handover solely includes POC. Beyond this, there was no specific order to the patients discussed; however, unwell patients were sometimes further prioritised, to allow the Registrar to review them immediately after handover.…”
Section: Interpretation Within the Context Of The Wider Literaturementioning
confidence: 99%
“…[1] This includes diagnosis, clinical condition, up-to-date management plans, and emerging critical information. [1,12] Our handover system includes free text boxes, with no minimum information required. Studies have demonstrated that free-text boxes are often insufficient for safe handover, and to be seen as useful by staff, electronic handovers must be simple, practical and informative.…”
Section: Interpretation Within the Context Of The Wider Literaturementioning
confidence: 99%
See 1 more Smart Citation